A systematic review of the Project Management Information Systems in different types of construction projects - Haloul, Mohamed Ibrahim Khalifa; Mohd Ariffin, Mohd Khairol Anuar; Supeni, Eris Elianddy; Ahmad, Siti Azfanizam; Bilema, Munder; Ahmad, Mushtaq (Universidad Camilo Jose Cela, 2024)
Project management information systems (PMIS) are software tools that help managers track projects from design to execution. PMISs are primarily developed to assist project management, but it is important to consider how well they adopt project management methods, how much assistance they provide at different phases of the project life cycle, and whether their scope is sufficient. This study investigated different types of PMISs, including web-based and software applications. The implementation of PMISs, their factors, and their effects on different types of projects (construction, manufacturing, IT, R&D, and finance) were also examined. Finally, future research directions were discussed. The study highlights the importance of comprehensive PMIS training programs to promote workplace learning, professional success, and project success. It emphasizes the need for organizations to select suitable PMIS software based on project complexity and scope, considering the financial implications and knowledge requirements. Furthermore, the implementation of a structured change methodology that integrates both the hard and soft aspects of change is recommended to facilitate effective change management within project-based organizations.